Plan de negocios para la exportación de malteadas nutricionales de la empresa Energía y Desarrollo SAS a la ciudad de Panamá (2018)
The purpose of this recent thesis (graduation project) is to proof the financial practicality (viability) for the exportation of nutritional smoothies to the city of Panama from Bogota, through the company of Energy and Development SAS. The viability studies will be based on finding the advantages and disadvantages, risks, investments and many other factors that come with exporting the product overseas.